Islamic Family Law Reform in Indonesia: A Review of the Supreme Court's Decision on the Postponement of the Distribution of Joint Property - Ritonga, Bakti; Mukhlas, Oyo Sunaryo; Nurrohman; Burhanuddin; Ridwan, Ahmad Hasan (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
The settlement of joint property between husband and wife after divorce often ends up in the Religious Court, even reaching the level of cassation and judicial review (PK), such as in the Supreme Court Decision Number Register 159/K/AG/2018. In this case, especially related to disputes over joint property in marriages with minor children, the Supreme Court not only refers to the normative law contained in the law, but also considers a sense of justice and benefit. This research uses a qualitative descriptive method with an empirical juridical approach. This approach is referred to as empirical legal research because it focuses on analyzing the implementation of normative legal provisions directly (in action) in certain legal events in society. Primary data was obtained from Supreme Court decision No 159 K/Ag/2018, No 618/Pdt.G/2012/PA.Bkt, No 38/Pdt.G/2013/PTA.Pdg, No 88K/Ag/2015, No 159/K/AG/2018, No 99/Pdt.G/2023/MS, as well as laws related to the research being discussed. Secondary data is obtained from books, scientific articles and previous research results related to joint property and those that have the same discussion. Data collection techniques using literature study and qualitative data analysis are used to explore certain phenomena and find out the causes. The results showed that the Supreme Court judge in deciding this case used the method of legal discovery through legal interpretation, especially systematic interpretation and sociological interpretation. In the case, the judge postponed the division of joint property until the children of the disputing parties reached the age of mumayyiz, thus showing attention to aspects of substantive justice. Systematic and sociological legal interpretations by judges show that in resolving post-divorce joint property disputes, especially those involving minors, judges must consider the social realities that live in society to actualize justice. This emphasizes the role of judges not only as law enforcers, but also as guardians of the public good. This research concludes that legal discovery by judges through interpretation based on systematic and sociological approaches can realize concrete justice in society, especially in divorce cases involving children.